2017
DOI: 10.1128/aac.01644-16
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Tedizolid in Methicillin-Resistant Staphylococcus epidermidis Experimental Foreign Body-Associated Osteomyelitis

Abstract: We developed a rat model of methicillin-resistant Staphylococcus epidermidis (MRSE) foreign body-associated osteomyelitis and used it to compare tedizolid alone and in combination with rifampin against rifampin alone, vancomycin plus rifampin, and vancomycin alone. A clinical strain of MRSE was inoculated into the proximal tibia, and a stainless steel wire with a precolonized MRSE biofilm was implanted. Following a 1-week infection period, 92 rats received either no treatment (n ϭ 17) or 14 days of intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…Previous studies confirmed the interaction between both drugs [ 3 , 13 , 26 ], as a result, serum linezolid levels decrease [ 10 , 11 ]. Interestingly, this effect between tedizolid and rifampicin was not found in preclinical studies [ 3 , 17 ]; however, well-designed clinical and pharmacokinetic studies are not available. In our experience, despite not determining the comparative serum levels of tedizolid when monotherapy or combination with rifampicin was used, we did not observe differences in the clinical outcome or the impact on hemoglobin or platelet counts in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies confirmed the interaction between both drugs [ 3 , 13 , 26 ], as a result, serum linezolid levels decrease [ 10 , 11 ]. Interestingly, this effect between tedizolid and rifampicin was not found in preclinical studies [ 3 , 17 ]; however, well-designed clinical and pharmacokinetic studies are not available. In our experience, despite not determining the comparative serum levels of tedizolid when monotherapy or combination with rifampicin was used, we did not observe differences in the clinical outcome or the impact on hemoglobin or platelet counts in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential advantages of tedizolid in osteoarticular infections (higher microbiological activity, advantageous pharmacokinetic/pharmacodynamics parameters, lower myelotoxicity, and drug–drug interactions) [ 1 , 2 , 3 ], clinical data on long-term treatment are scarce [ 16 ]. Knowledge is limited to a few experimental studies [ 17 , 18 , 19 ], case reports [ 20 ] and recently some case series in which tedizolid is prescribed for different indication including osteoarticular infections [ 21 , 22 ]. Thus, in the present study, we intend to describe our multicenter experience within the Spanish Network for Research in Infectious Diseases (REIPI) with long-term use of tedizolid in a cohort of patients with osteoarticular and diabetic foot infections and focused on the efficacy and safety in monotherapy or combination.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria strains used in these studies were UAMS-1 [ATCC 49230 ( 47 )], USA-300 [ATCC BAA-1556 ( 61 )], Xen29 [PerkinElmer ( 62 )], 46,106 (CDC Clinical and Environmental Microbiology Branch Culture Collection), and IDRL-8883 [clinical isolate ( 63 )] and are compiled in SI Appendix , Table S1 . All strains were cultured on trypic soy agar (TSA) plates (BD Diagnostics) at 37 °C unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…TZD has a high oral bioavailability and can be administered once-daily; furthermore, drug–drug interactions with mono-amine oxidase inhibitors (MAOI), serotonin-reuptake inhibitors (SRI) or rifampicin are unlikely, although the latter has recently been questioned [ 21 , 22 ]. Recent in vitro and animal studies suggested that the addition of rifampicin to TZD was likely to achieve a synergistic effect against methicillin-resistant Staphylococcus aureus (MRSA) and S. epidermidis , and prevent the emergence of rifampicin-resistant mutants [ 23 , 24 ]. While TZD appears to be an attractive candidate for the treatment of PJIs due to gram-positive cocci, and has shown satisfactory efficacy and tolerability in clinical trials, data about its tolerability and compliance in long-term treatments are lacking.…”
Section: Introductionmentioning
confidence: 99%